The Surgical Management of the Mesentery in Crohn's Disease - Coffey, J.C.; Devine, M.L. (Clinics in Colon and Rectal Surgery, 2024)
Increasing evidence suggests that Crohn's disease is a primary mesenteropathy and that resection of the mesentery, or its exclusion from an anastomosis, may alter disease progression. If borne out in clinical trials, this observation would be welcome, as current pharmacotherapeutic approaches to Crohn's disease appear to have limited effect on disease progression. This article explores arguments for and against the alteration of mesenteric inputs by surgical means, in Crohn's disease.
Keywords: Crohn's disease; mesentery; resection; Kono-S; recurrence